In Vitro Evaluation of Green Tea Extract's Influence on Local Sheep - Rahmatillah, Ririn Siti; Ramdani, Diky; Hernaman, Iman; Jayanegara, Anuraga (UIN Sunan Gunung Djati Bandung, 2024)
In recent years, the exploration of natural supplements such as green tea extract and their potential benefits in livestock nutrition has gained considerable attention among researchers and agriculturalists. Green tea extract contains a high concentration of bioactive substances, such as polyphenols and catechins. This study aimed to explore the effects of varying doses of green tea extract on rumen fermentation parameters through an in vitro trial using sheep rumen liquids. A completely randomized experimental design was utilized to test the effect of 4 different doses of green tea extract treatments (0, 140, 280, and 560 mg/kg) on in vitro Hohenheim gas test method. The current study shows no significant effect of administering green tea extract at various doses on total gas production, total gas production per in vitro dry matter and organic matter degradability, volatile fatty acid per in vitro dry matter and organic matter degradability, methane production per inv vitro dry matter and organic matter degradability of green tea extract. Although no significant effects were observed on the investigated parameters, this study provides important insights in the understanding of the potential use of green tea extract in modulating fermentation processes in the ruminant’s stomach. In conclusion, the findings of this study underscore the impact of GTE on gas production regulation, highlighting its potential implications for gastrointestinal health